1990
DOI: 10.1063/1.346679
|View full text |Cite
|
Sign up to set email alerts
|

Effects of noble gases on diamond deposition from methane-hydrogen microwave plasmas

Abstract: The deposition of diamond films by microwave plasmas has been studied in gaseous mixtures of methane, hydrogen, and noble gases. Plasma diagnostic results are compared with growth rates and Raman spectra of the films. The noble gases, which influence the degree of excitation or reactant molecules by energy transfer or charge transfer from their excited and ionic states, are active in the deposition process by inducing additional ion-molecule and excited atom-molecule reactions. As a result, enhanced deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(43 citation statements)
references
References 20 publications
0
43
0
Order By: Relevance
“…Density functional theory ͑DFT͒ calculations, 34 motivated by the experimental observation of deposition of diamond films by C 2 produced from C 60 fragmentation in hydrogen poor plasmas, 47,48 showed that growth by C 2 at a bare ͑i.e., not H terminated͒, clean diamond ͑110͒ surface is also energetically favored, and presents only very low energy barriers to the formation of C 2n chains and, ultimately, new layers. Although there have been reports of increasing C 2 concentrations in low power microwave plasmas that are correlated with degraded diamond film quality, 49,50 Gruen et al observed a positive correlation between C 2 emission and the film growth rate, and OES studies by our group 6 and by others 8 demonstrated that growth of high quality diamond films can proceed hand in hand with strong C 2 dϪa emission in more highly activated gas plasma environments.…”
Section: Discussionmentioning
confidence: 93%
“…Density functional theory ͑DFT͒ calculations, 34 motivated by the experimental observation of deposition of diamond films by C 2 produced from C 60 fragmentation in hydrogen poor plasmas, 47,48 showed that growth by C 2 at a bare ͑i.e., not H terminated͒, clean diamond ͑110͒ surface is also energetically favored, and presents only very low energy barriers to the formation of C 2n chains and, ultimately, new layers. Although there have been reports of increasing C 2 concentrations in low power microwave plasmas that are correlated with degraded diamond film quality, 49,50 Gruen et al observed a positive correlation between C 2 emission and the film growth rate, and OES studies by our group 6 and by others 8 demonstrated that growth of high quality diamond films can proceed hand in hand with strong C 2 dϪa emission in more highly activated gas plasma environments.…”
Section: Discussionmentioning
confidence: 93%
“…15,16 An earlier paper by Zhu et al used a tubular microwave plasma reactor and reported diamond film growth rates and some emission intensity data. The dependence on the Ar fraction was very different from ours, but the correlation between C 2 emission and growth rate appears similar.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of C 2 results in a very high re-nucleation rate; such conditions are typically used to deposit nanocrystalline diamond thin films. [7,8] No additional hydrogen was added to the plasma during the MPECVD step (aside from a small amount added to the system to stabilize the plasma at the very beginningÐrelative hydrogen percentage of 2 % for approximately 10 min). Although great care was taken to extract as much hydrogen from the system as possible, the decomposition of CH 4 in the MPECVD system results in a small amount of hydrogen in the gas phase during deposition (1.5 %).…”
mentioning
confidence: 99%